Hermeneutika Fenomenologis Martin Heidegger dan Relevansinya terhadap Interpretasi Realitas Keagamaan dalam Islam Kontemporer - Rifatun Sofiah; Maragustam Siregar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The development of contemporary Islamic religiosity in the modern and digital era has brought significant transformations in the ways Muslims understand, experience, and express their religious life. The dominance of positivistic approaches in religious studies has often reduced the existential, experiential, and spiritual dimensions of religion. This study aims to analyze the relevance of Martin Heidegger’s phenomenological hermeneutics in interpreting the reality of contemporary Islamic religiosity and to explore the possibility of a methodological dialogue between Heideggerian philosophy and ‘irfani epistemology within the Islamic intellectual tradition. This research employs a qualitative library-based method by utilizing Heidegger’s phenomenological hermeneutic framework, particularly the concepts of Dasein, being-in-the-world, thrownness, and fallenness as analytical tools. The findings indicate that contemporary Islamic religiosity should not be understood merely as a normative system, but as an existential experience shaped by historical, social, and digital contexts. Digital transformation has influenced religious authority, encouraged performative forms of religiosity, and contributed to the fragmentation of religious meaning in modern Muslim societies. Furthermore, the study identifies a methodological convergence between Heideggerian hermeneutics and ‘irfani epistemology, especially in the dimension of pre-reflective human experience. This study concludes that phenomenological hermeneutics offers an alternative interpretative framework that is more contextual, reflective, existential, and responsive to the dynamics of digital religiosity in contemporary Islam.